Vigour control in apple (Malus domestica) and kiwifruit ((Actinidia deliciosa and Actinidia chinensis) : a thesis presented in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Plant Physiology at Massey University, Palmerston North, New Zealand - Vattiprolu, Noveline Mercy Rose Gali (Massey University, 2012)
Recent knowledge suggests the physiological basis of scion vigour control by dwarfing apple rootstocks involves shoot-root-shoot hormonal signalling. An aim of the present study was to further explore the role of gibberellin in control of apple (Malus domestica) scion vigour on a dwarfing rootstock and also an attempt was made to elucidate whether a generalised signalling mechanism exists in kiwifruit vines. For commercially grown kiwifruit (Actinidia deliciosa and Actinidia chinensis), there have been no studies on whether gibberellins stimulate the vigorous shoot growth that normally occurs. For apple, dwarfing rootstocks of Malling Nine (‘M.9’) and vigorous rootstocks ‘Royal Gala’ (‘RG’) were grafted with scions of ‘M.9’ or ‘RG’ using a reciprocal grafting treatment structure. The ‘M.9’ rootstock increased the proportion of ‘RG’ primary shoots that terminated early with reduced growth rate and plastochron while exogenous gibberellins partially reversed the effect by stimulating both apical and sub-apical meristems and prolonging shoot extension, thus suggesting that ‘RG’ scions on ‘M.9’ rootstocks were deficient in bioactive gibberellins. The gibberellin foliar sprays increased the internode length by acting on cell division primarily and on cell elongation secondarily. The ‘M.9’ shoots of apple are short with reduced node number and early termination compared to vigorous ‘RG’ plants. This low vigour phenotype was maintained even on the vigorous rootstock, ‘RG’. Foliar sprays of GA3+GA4+7 to the scion did not reverse the primary or sylleptic shoot growth of ‘M9’ scion, which suggests that ‘M.9’ may be unable to convert exogenous gibberellins to bioactive GA1. For kiwifruit, the auxin transport inhibitor 1-N-naphthylphthalamic acid (NPA) applied to the stem of young rooted stem cuttings of Actinidia chinensis ‘Hort16A’ significantly reduced primary shoot length but the architectural changes imposed were different from those of NPA applied to apple. For apple, both NPA and a dwarfing rootstock reduced number and length of sylleptic axillary shoots (SAS) on the primary shoot and caused early termination of both SAS and primary shoots, whereas for kiwifruit NPA did not have any effect on total shoot growth compared with control. Given these dissimilarities, it was proposed the reduction of indole-3-acetic acid (IAA) to the root system of kiwifruit may not affect shoot growth through an effect on root-produced hormones. However, more work is needed using different auxin transport inhibitors to evaluate the effect of auxin restriction to the root system on root-produced hormones. Foliar sprays of 1-naphthaleneacetic acid (NAA) and NPA reduced total shoot length of kiwifruit ‘Hayward’, possibly due to supra-optimal synthetic auxin levels for NAA and low levels of natural auxin levels for NPA in kiwifruit stems respectively. Foliar sprays of 500-1000 mg L-1 gibberellins (GA3+GA4+7) applied to mature ‘Hayward’ vines was found to be optimum for stimulating vigorous shoot growth. Since the anti-gibberellin prohexadione-Ca, decreased kiwifruit shoot growth, it may be possible to use this compound commercially to control excessive vegetative growth. As this anti-gibberellin inhibits the action of enzyme GA20 oxidase, which promotes the ultimate step of converting GA20 and GA19 to GA1 in GA-biosynthesis pathway, it may also be possible to suppress the expression of gene encoding GA20 oxidase with the help of molecular biology techniques or produce better rootstock by conventional breeding. Gibberellins activity in stimulating apical and sub-apical meristem is the most important event involved in shoot extension growth of kiwifruit and apple. For both kiwifruit and apples exogenous gibberellins inhibited flowering. For composite apple tree rather surprisingly, the ‘RG’ rootstock promoted flowering for ‘RG’ scion whereas ‘M.9’ rootstock reduced flowering. For kiwifruit, BAP promoted a high percentage of synchronised bud breaks. For both apple and kiwifruit gibberellins GA3+GA4+7 appeared to stimulate sylleptic axillary shoot formation. For kiwifruit the possibility exists to select low vigour seedling, increase their vigour with gibberellins during the establishment phase, and then decrease vigour by withholding gibberellins once the canopy is established.
Keywords: Apples; Kiwifruit; Vigour; Vitality